A corrosion map of Abu Dhabi. Issue 3 (13th July 2011) - Cole, I. S.; Ganther, W. D.; Helal, A. M.; Chan, W.; Paterson, D.; Trinidad, G.; Corrigan, P.; Mohamed, R.; Sabah, N.; Al‐Mazrouei, A.
Abstract This paper outlines how a corrosion map of zinc was developed for Abu‐Dhabi. It presents inputs into the model being databases of RH, rainfall, salt deposition and time of wetness and explains how these inputs are combined to product the corrosion map of Abu Dhabi. It is found that although the corrosion rate generally falls with distance from the Arabian Gulf, corrosion rates in the hinterland of the central coast and in the Hajar Mountains are higher than would be expected from a simple dependence on distance from the coast. The higher corrosion rates around the central coast are associated with the extremely low rainfall while those in the Hajar Mountains may be associated with the transport of airborne salinity from the Gulf of Oman. In general, the corrosion rates in Abu Dhabi are much higher than observed at sites in Australia and South East Asia with similar levels of airborne salinity which is attributed to the much higher quantities of salt that are retained on metal surfaces in Abu Dhabi (relative to Australia) due to the fact that rain washing events, which are frequent and effective in Australia, are very infrequent in Abu Dhabi.